PELATIHAN PENGUATAN SDM UNTUK MENGOPTIMALKAN PENGELOLAAN DIGITAL DI DESA MANGKUBUMI - Toto, Toto; Iskandar, H Yusup; Kasman, Kasman (Jurnal Abdi Insani, 2025)
This community service is carried out as a solution to strengthening digital villages in Mangkubumi Village, Sadananya District. The Human Resources and Digital Village facilities in Mangkubumi Village itself are qualified, but their management is not optimal. The training was carried out directly in Leuwihalang Hamlet, Mangkubumi Village, Sadananya District. This training was aimed at the Karang Taruna of Mangkubumi Village as many as 10 people. In the training process the service team presents two presenters with different content. The service team takes material that will be delivered by the speaker regarding news writing and graphic design. Training is held 3 times a week with a series of training activities, namely presentation sessions, discussions, and writing training. Human Resource Strengthening Training to Support Digital Village Management in Mangkubumi Village has been carried out. Karang Taruna Desa understands how to optimize digital village management in Mangkubumi Village. Strengthening Human Resources Through Digital Literacy in accordance with the needs of the Village Youth Organization, where so far Mangkubumi Village has qualified Human Resources and Digital Village facilities. This training can certainly give birth to youth from Mangkubumi Village who are qualified to manage Digital Villages. Keywords :